Natural abundance of 18O of sugar biomarkers in topsoils along a climate transect over the Central Scandinavian Mountains, Norway†. Issue 1 (13th February 2013) - Zech, Michael; Tuthorn, Mario; Glaser, Bruno; Amelung, Wulf; Huwe, Bernd; Zech, Wolfgang; Zöller, Ludwig; Löffler, Jörg
Abstract Precipitation and topsoil samples from a climate transect over the Scandinavian Mountains, Norway, were analyzed for bulk and compound‐specific δ18O values. The natural abundance of 18O in the plant‐derived hemicellulose biomarkers arabinose and xylose correlates positively with δ18O of bulk soil, but not with δ18O of precipitation. This suggests that other factors than δ18Oprec, such as evaporative 18O enrichment of leaf water, exert a strong influence on the natural abundance of 18O in soils.